Nervous system delivery of antilysophosphatidic acid antibody by nasal application attenuates mechanical allodynia after traumatic brain injury in rats - Eisenried, Andreas; Meidahl, Anders C. N.; Klukinov, Michael; Tzabazis, Alexander Z.; Sabbadini, Roger A.; Clark, J. David; Yeomans, David C. (Pain, 2017)
Lysophosphatidic acid (LPA) is a bioactive lipid that impacts neurological outcomes after neurotrauma by inhibiting neuroregeneration, promoting inflammation, and contributing to behavioral deficits. Blocking LPA signaling with a novel anti-LPA monoclonal antibody (mAb) is neuroprotective after traumatic brain injury (TBI) if given to injured animals whose blood-brain barrier (BBB) has been compromised. It is hypothesized that the anti-LPA mAb could improve chronic pain initiated by TBI. However, poor brain penetration after systemic application of the antibody makes access to the central nervous system (CNS) problematic in situations where the BBB is intact. Our experiments investigated whether intranasal delivery of the anti-LPA mAb could bypass the BBB, allowing for direct entry of the antibody to certain areas of the CNS. When the humanized anti-LPA mAb, LT3114, was intranasally applied to injured rats within 30 minutes after mild TBI using the central lateral percussion model, enzyme-linked immunospecific assay and immunohistochemistry demonstrated antibody uptake to several areas in the CNS, including the area of cortical injury, the corpus callosum, cerebellum, and the subventricular region. Compared with control rats that received LT3114 but no TBI, TBI rats demonstrated significantly higher concentrations of intranasally administered LT3114 antibody in some tissues. In behavioral studies, a significant attenuation of mechanical allodynia after TBI was observed in the anti-LPA treatment group (P = 0.0079), when compared with vehicle controls within 14 days after TBI. These results suggest that intranasal application of the anti-LPA antibody directly accesses CNS sites involved in TBI-related pain and that this access attenuates pain sequelae to the neurotrauma.
EVALuna2:36285